Editorial of Special Issue “Multiple Sclerosis: From Diagnostic Biomarkers to Imaging and Clinical Predictors” - Jakimovski, Dejan; Zivadinov, Robert (Diagnostics (Basel), 2022)
The presence of higher EDSS scores and lower whole brain volume at the baseline visit were both predictors of isolated cognitive decline. [...]40% of these patients were already classified as cognitively impaired at baseline [4]. [...]early detection of cognitive impairment can identify patients that are at risk for additional future cognitive decline. [...]streamlines of the uncinate fasciculus, inferior longitudinal fasciculus and corpus callosum were associated with verbal episodic and semantic memory performance [5]. [...]the work by Jewells et al. utilizes novel in vivo detection of microglia through PET detection of 18-kDa translocator protein (TSPO) radiotracer in demyelinating mice model of MS [13].